2016
DOI: 10.1111/bjet.12483
|View full text |Cite
|
Sign up to set email alerts
|

Podcasts: A technology for all?

Abstract: While the pedagogical benefits and challenges of podcasting as a teaching and learning practice are well researched, sometimes with contradictory results, literature on the potential of podcasting as a socially inclusive technology is scanty. Using a quantitative survey design, framed by concepts such as emerging technologies, low‐threshold applications and nontraditional students, this study investigated students perceptions at a large institution in South Africa on the access and use of podcasts. Findings in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 15 publications
0
17
0
1
Order By: Relevance
“…Other publish and share tools, such as Podcasts (7) were used with the same aim as video technologies, for more transmissive practices such as registering class moments, and facilitate students access to it settings outside of class (Gachago, Livingston, & Ivala, 2016). Students tended to perceive podcasts as a useful tool to support learning, and being easy to use, predicting their acceptance to use this tool for learning (Jiménez-Castillo, Sánchez-Fernández, & Marín-Carrillo, 2017;Merhi, 2015;Tolulope, Adenubi, & Oluwole, 2015;Zacharis, 2012).…”
Section: Publish and Sharementioning
confidence: 99%
“…Other publish and share tools, such as Podcasts (7) were used with the same aim as video technologies, for more transmissive practices such as registering class moments, and facilitate students access to it settings outside of class (Gachago, Livingston, & Ivala, 2016). Students tended to perceive podcasts as a useful tool to support learning, and being easy to use, predicting their acceptance to use this tool for learning (Jiménez-Castillo, Sánchez-Fernández, & Marín-Carrillo, 2017;Merhi, 2015;Tolulope, Adenubi, & Oluwole, 2015;Zacharis, 2012).…”
Section: Publish and Sharementioning
confidence: 99%
“…In quantitative studies the experimental method was the most widely used (e.g., [44]), followed by the quasi-experimental method (e.g., [49]), other studies use an exploratory [50] and descriptive scope [51]. In mixed studies the quasi-experimental method was the most widely used (e.g., [52]), followed by the case study (e.g., [15], [42]).…”
Section: !"#$%And$ Research Methodology!mentioning
confidence: 99%
“…It is important to clarify that the total does not correspond to the total number of studies, because this study used several instruments for data collection (e.g., [50], [9] Table 3 shows that the survey is the main instrument of data collection, followed by the interview (semi-structured, structured) and then, the observation (participant and non-participant). On the other hand, the questionnaire, the products generated within the research by some of the participants of the educational process, the prepost test and the focus groups were used to a lesser extent and finally studies were found that used rubrics to collect information (e.g., [51])…”
Section: !"#$%And$ Research Methodology!mentioning
confidence: 99%
“…Investigações com foco no uso de tecnologias digitais por estudantes não tradicionais têm sido reduzidas, contudo, há alguns estudos que referem à valorização que esses estudantes fazem do seu uso como suporte à aprendizagem, alertando para a necessidade de adaptar e selecionar as tecnologias a usar tendo em consideração os níveis de competências digitais. Indicam, ainda, que em estudantes com esse perfil acadêmico esses níveis são frequentemente baixos (KELLY et al, 2009;GACHAGO;LIVINGSTON;IVALA, 2016; PADILLA-CARMONA; SUÁREZ-ORTEGA; SÁNCHEZ-GARCÍA, 2016). Importa, antes de apresentarmos alguns desses estudos, caracterizar a que tipo de estudantes nos estamos a referir.…”
Section: Introductionunclassified